2016
DOI: 10.1136/bmjopen-2016-013282
|View full text |Cite
|
Sign up to set email alerts
|

Exploring educational needs and design aspects of internet-enabled patient education for persons with diabetes: a qualitative interview study

Abstract: ObjectiveThe objective of this article is to explore the educational needs and design aspects of personalised internet-enabled education for patients with diabetes in Iran.DesignData were collected using semistructured interviews and then qualitatively analysed using inductive content analysis.Participants9 patients with type 2 diabetes were included. Inclusion criteria were access to and knowledge on how to use the internet. The selection ensured representation based on gender, age, occupation and educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The electronic search results identified a total of 4,233 abstracts and 259 articles were subjected to a full text review, of which 15 papers met the inclusion criteria [31][32][33][34][35][36][37][38][39][40][41][42][43]. Cumulatively, the articles included a total of 270 adult patients with type 2 diabetes mellitus and HCPs, with five studies originating from the United States, five from the United Kingdom, three from Canada and one from Iran and Belgium respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic search results identified a total of 4,233 abstracts and 259 articles were subjected to a full text review, of which 15 papers met the inclusion criteria [31][32][33][34][35][36][37][38][39][40][41][42][43]. Cumulatively, the articles included a total of 270 adult patients with type 2 diabetes mellitus and HCPs, with five studies originating from the United States, five from the United Kingdom, three from Canada and one from Iran and Belgium respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There were five types of interventions used in the papers. Nine papers used a web-based interventions [32,33,35,36,[39][40][41][42][43][44], while the others used either a mobile phone applications (apps) [38,45], a digital versatile disc (DVD) [34], virtual reality [31], or telehealth [37]. Three studies also explored the HCPs' views on this subject [34,37,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient education is an important and recommended non-pharmacological treatment for patients with different chronic diseases, including SpA [ 22 , 23 ]. Earlier studies in the field have concentrated on patients with rheumatoid arthritis, and not much research has been done in patients with SpA [ 11 , 31 ]. The results from the present study showed that almost half of the patients with SpA considered that they had a need for education, and the areas concerning self-help, feelings, and the disease process were those that were most requested.…”
Section: Discussionmentioning
confidence: 99%
“…Individually tailored education have been requested [ 7 ] but often the prioritisation of topics to be discussed still differs between patients and health professionals [ 5 ]. Patient education has spread more widely than within healthcare itself, with e-health and web-based health resources such as telehealth platforms, online communication services, and smartphones emerging as new methods of communication and education [ 3 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%